2003
DOI: 10.1063/1.1568152
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of chromium (IV, V, VI) in Cr:Li2MSiO4 (M=Mg,Zn)

Abstract: To understand the exceptionally long fluorescence lifetime of Cr IV in Li 2 MSiO 4 (M ϭMg,Zn), several spectroscopic investigations are performed on Cr:Li 2 MSiO 4 (M ϭMg,Zn) crystals. X-ray absorption near-edge structure investigations attest that chromium is localized in tetrahedral sites and that Cr VI is the major species while Cr IV is the minor one in both compounds. Electron paramagnetic resonance studies confirm the occurrence of Cr V in elongated tetrahedral environment (d x 2 Ϫy 2 ground state͒, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…(ii) The energy position of the chromium K-edge, corresponding to the minimum energy required to promote a 1s electron to the continuum, is very sensitive to the chromium oxidation state, to the electronegativity of the nearest neighbor atoms, and to the coordination geometry. These results have been confirmed by recent studies, , which demonstrated that there is a direct correlation between the energy position of the edge and/or the preedge and the valence state of the chromium center. This means that in principle, it should be possible to use the position of the Cr−K edge and preedge transitions to determine the average chromium valence state and coordination geometry in unknown compounds, by using data collected for reference compounds.…”
Section: 41 Xanessupporting
confidence: 81%
“…(ii) The energy position of the chromium K-edge, corresponding to the minimum energy required to promote a 1s electron to the continuum, is very sensitive to the chromium oxidation state, to the electronegativity of the nearest neighbor atoms, and to the coordination geometry. These results have been confirmed by recent studies, , which demonstrated that there is a direct correlation between the energy position of the edge and/or the preedge and the valence state of the chromium center. This means that in principle, it should be possible to use the position of the Cr−K edge and preedge transitions to determine the average chromium valence state and coordination geometry in unknown compounds, by using data collected for reference compounds.…”
Section: 41 Xanessupporting
confidence: 81%
“…For these reasons, XAFS spectroscopies are, in principle, powerful techniques to understand the local structure and the oxidation state of Cr species on the Phillips catalyst. Nevertheless, in contrast to the large amount of XANES studies on various chromium compounds reported in the past, only few XAFS works appeared on the Phillips catalyst or on related systems, ,,,, and only one is focused on in situ C 2 H 4 polymerization . Three main reasons could be tentatively accounted for this lack.…”
Section: Cr/sio2 Phillips Catalyst: In Situ Ethylene Polymerizationmentioning
confidence: 99%
“…For the reasons outlined above, EXAFS spectroscopy is, in principle, a powerful technique to understand the local structure of grafted Cr species on the Phillips catalyst. Nevertheless, in contrast to the large amount of XAS studies on various chromium compounds reported in the past, [64][65][66][67][68][69] only a few works appeared about XAS applied on the Phillips catalyst or on related systems. 9,[70][71][72][73][74][75][76] This is mainly due to the low Cr loading (in the 0.5-1.0 wt% range) and its high reactivity towards oxygen and moisture.…”
Section: Structural Techniques (Xrpd and Exafs)mentioning
confidence: 99%